Method for preparing composite solid electrolyte through Lewis fluorine supply nano additive
By using Lewis-supplied fluorine nano additives in lithium-ion batteries, the problems of low ion conductivity and uneven polymerization reaction of solid electrolytes in the prior art are solved, and the high stability and cycling performance of the battery are achieved.
Patent Information
- Application Number
- CN202411593293.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The solid electrolyte in existing lithium-ion batteries has low ion conductivity and uneven polymerization reactions, which affects the stability and cycling performance of the battery.
The composite solid electrolyte is prepared by using the Lewis fluorine nano additive, and the in-situ curing process is adopted to avoid additional initiators, and the polymerization reaction is initiated by the decomposition reaction of the lithium salt in the heating state.
The polymerization reaction is achieved without additional initiators, ensuring the uniformity of the polymerization reaction and high ionic conductivity, and improving the stability, magnification and cycling performance of semi-solid lithium-ion batteries.
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a method for preparing a composite solid electrolyte by using Lewis fluorine-donating nano-additives. Background Art
[0002] Lithium-ion batteries have the advantages of high energy density and low self-discharge, and have become the most widely used electrochemical energy storage devices. They have been widely used in digital products, new energy vehicles and other fields. Currently, most of the commercial lithium-ion batteries use organic liquid electrolytes, but the energy density of liquid lithium batteries is close to a bottleneck. At the same time, they can cause fires and explosions when encountering extreme situations such as punctures and short circuits. Compared with the safety issues brought about by traditional organic electrolytes, the use of solid electrolytes can greatly reduce the combustible components in the battery, greatly improving the safety performance of the battery.
[0003] Polymer solid electrolytes have good flexibility and excellent interface contact, which can greatly improve the safety and cycle performance of existing lithium-ion batteries. At present, the process route of semi-solid batteries often adopts in-situ curing, but the initiators added in the in-situ curing process, such as azobisisobutyronitrile (AIBN) or benzamide peroxide (BPO), have poor compatibility with the positive and negative electrodes. The amount of addition needs to be strictly controlled and the polymerization process cannot be accurately controlled. The residual initiator will deteriorate the electrical performance of the battery, and the low ionic conductivity of the polymer and the damage to the material caused by the high temperature of in-situ polymerization will have a serious impact on the electrical performance of the later battery.
[0004] In order to solve the above problems and avoid the use of free radical polymerization (which requires additional initiators), Lewis acids are used to efficiently initiate cationic polymerization of epoxy precursors. However, the ionic conductivity of solid electrolytes that are only polymerized by cationic in situ is low, and there may be uneven polymerization reactions. Therefore, it is necessary to develop a method for preparing composite solid electrolytes using Lewis fluorine-donating nanoadditives. Summary of the invention
[0005] The present application provides a method for preparing a composite solid electrolyte by using Lewis fluorine-donating nano-additives to solve the problems of low ionic conductivity of solid electrolytes in the prior art and possible uneven polymerization reaction, thereby achieving the characteristics of no need for additional initiators, uniform polymerization reaction, high ionic conductivity, etc., and being able to improve the stability, rate and cycle performance of semi-solid lithium-ion batteries.
[0006] The present application provides a composite solid electrolyte prepared by using Lewis fluorine-donating nano additives. The composite solid electrolyte components include 10-20 parts of polymer monomers, 2-6 parts of lithium salts, 1-4 parts of nano functional additives and 5-12 parts of organic solvents in parts by weight.
[0007] Preferably, the polymerization monomer is a cycloalkane ether monomer or an olefin ether monomer, and the cycloalkane ether monomer includes at least one of ethylene oxide, 1,2-propylene oxide, tetrahydrofuran, 1,3-dioxolane, 1,4-dioxane, polyethylene glycol methyl ether methacrylate, and polyethylene glycol methyl ether acrylate.
[0008] Preferably, the lithium salt includes any one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(difluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, and lithium difluorooxalatoborate, or a combination of at least two thereof.
[0009] Preferably, the nano functional additive is a Lewis acid fluorine supply additive, including any one of nano aluminum trifluoride and nano boron trifluoride, or a combination of both.
[0010] Preferably, the organic solvent includes any one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl formate, tetrahydrofuran, acetone, methyl pyrrolidone, and acetonitrile, or a combination of at least two thereof.
[0011] Preferably, a method for preparing a composite solid electrolyte by using a Lewis fluorine-donating nano-additive comprises the following steps:
[0012] A. Mixing a polymerization monomer, a lithium salt, a nano-functional additive and an organic solvent to obtain an in-situ solidified electrolyte precursor;
[0013] B. Inject the in-situ curing electrolyte precursor into the battery cell, let it stand for 1 minute under a vacuum of -80 kPa, and let it stand for 12-48 hours in an environment of 20-35°C after vacuum packaging. The pressure during curing is 0.6-3 MPa, and it is cured at 45-80°C for 4-12 hours to obtain an in-situ curing composite solid electrolyte.
[0014] Preferably, based on the total mass of the in-situ solidified electrolyte precursor as 100%, the mass percentage of the polymerized monomer is 10%-20%; the mass percentage of the lithium salt is 15-30%; the mass percentage of the functional additive is 0%-10%; and the mass percentage of the organic solvent is 40%-75%.
[0015] Beneficial effects:
[0016] (1) The preparation method of the present invention is simple. When the composite solid electrolyte is used in lithium-ion batteries, it has the characteristics of no need for additional initiators, uniform polymerization reaction, high ion conductivity, etc., and can improve the stability, rate and cycle performance of semi-solid lithium-ion batteries.
[0017] (2) In the present invention, no additional initiator is added to the raw materials for preparing the in-situ solidified solid electrolyte. The lithium salt is unstable and decomposed into Lewis acid under heating. The Lewis acid is used to efficiently initiate the ring-opening of the cyclic ether for polymerization reaction. No initiator remains, and no additional side reactions will occur to cause the battery performance to deteriorate. Specifically, in the absence of external heating conditions, the heat of dissolution of lithium salts such as lithium hexafluorophosphate is sufficient to promote its partial decomposition and release a small amount of phosphorus pentafluoride. In the precursor solution, phosphorus pentafluoride combines with trace water to form H + (PF5OH) - , H + (PF5OH) - The DOL monomer is induced to transform into a reactive second oxonium ion through rapid protonation, and the DOL monomer is repeatedly inserted into the oxonium ion to grow the polymer chain.
[0018] (3) The nano-functional additive in the present invention is a Lewis fluorine-supplying additive, which has three main functions: on the one hand, nano-AlF3 has a Lewis acid center, which can be hydrolyzed to form a Lewis acid under heating and other conditions, and can effectively catalyze the ring-opening polymerization reaction to improve the polymerization efficiency; the Lewis fluorine-supplying additive has a strong adsorption effect on lithium salt anions, which can promote the dissociation of lithium salts, inhibit the formation and migration of anion clusters [Li(TFSI)2]-, and thus provide more free Li+, improve the ionic conductivity of the electrolyte and the number of lithium ion migration, and can reduce the electrode pole to achieve high rate performance of the battery; the nanomaterial can be well dispersed on the surface of the positive and negative electrode materials to form a good solid / solid interface with the polymer electrolyte. At the same time, the nanomaterial has a large specific surface area and a high catalytic activity. The nano-additive can effectively adsorb the polymerization monomer of the polymerization reaction and serve as a polymerization reaction catalytic center to make the in-situ polymerization reaction more uniform and form a solid electrolyte with uniform polymerization reaction and high ionic conductivity.
[0019] The above description is only an overview of the technical solution of the embodiment of the present application. In order to more clearly understand the technical means of the embodiment of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the embodiment of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. DETAILED DESCRIPTION
[0020] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used in the specification of the application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0022] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase "embodiments" in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0023] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application is clearly and completely described below.
[0024] The present application provides a composite solid electrolyte prepared by using Lewis fluorine-donating nano additives. The composite solid electrolyte components include 10-20 parts of polymer monomers, 2-6 parts of lithium salts, 1-4 parts of nano functional additives and 5-12 parts of organic solvents in parts by weight.
[0025] Embodiment 1:
[0026] The composite solid electrolyte components include 10 parts of polymer monomers, 2 parts of lithium salts, 1 part of nano functional additives and 5 parts of organic solvents in parts by weight.
[0027] In this embodiment, the polymerization monomer is a cycloalkane ether monomer or an olefin ether monomer, and the cycloalkane ether monomer includes a mixture of ethylene oxide, 1,2-propylene oxide, and tetrahydrofuran.
[0028] In this embodiment, the lithium salt includes a mixture of lithium hexafluorophosphate and lithium tetrafluoroborate.
[0029] In this embodiment, the nano functional additive is a Lewis acid fluorine supplying additive, including nano aluminum trifluoride.
[0030] In this embodiment, the organic solvent includes a mixture of ethylene carbonate and propylene carbonate.
[0031] In this embodiment, a method for preparing a composite solid electrolyte using a Lewis fluorine-donating nano-additive comprises the following steps:
[0032] A. Mixing a polymerization monomer, a lithium salt, a nano-functional additive and an organic solvent to obtain an in-situ solidified electrolyte precursor;
[0033] B. Inject the in-situ solidified electrolyte precursor into the battery cell, let it stand for 1 minute under a vacuum of -80 kPa, evacuate and package it, let it stand for 12 hours in a 20°C environment, the pressure during curing is 0.6 MPa, and cure it at 45°C for 4 hours to obtain an in-situ solidified composite solid electrolyte.
[0034] In this embodiment, taking the total mass of the in-situ solidified electrolyte precursor as 100%, the mass percentage of the polymerized monomer is 10%; the mass percentage of the lithium salt is 15%; the mass percentage of the functional additive is 1%; and the mass percentage of the organic solvent is 74%.
[0035] Embodiment 2:
[0036] The composite solid electrolyte components include 20 parts of polymer monomers, 6 parts of lithium salts, 4 parts of nano-functional additives and 12 parts of organic solvents in parts by weight.
[0037] In this embodiment, the polymerization monomer is a cycloalkane ether monomer or an olefin ether monomer, and the cycloalkane ether monomer includes a mixture of tetrahydrofuran, 1,3-dioxolane, and 1,4-dioxane.
[0038] In this embodiment, the lithium salt includes a mixture of lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium bis(difluorosulfonyl)imide.
[0039] In this embodiment, the nano functional additive is a Lewis acid fluorine supplying additive, including nano boron trifluoride.
[0040] In this embodiment, the organic solvent includes dimethyl carbonate, diethyl carbonate, and a mixture of methyl and ethyl carbonate.
[0041] In this embodiment, a method for preparing a composite solid electrolyte using a Lewis fluorine-donating nano-additive comprises the following steps:
[0042] A. Mixing a polymerization monomer, a lithium salt, a nano-functional additive and an organic solvent to obtain an in-situ solidified electrolyte precursor;
[0043] B. Inject the in-situ curing electrolyte precursor into the battery cell, let it stand for 1 minute under a vacuum of -80 kPa, evacuate and package it, and let it stand for 16 hours in a 35°C environment. The pressure during curing is 3 MPa, and it is cured at 80°C for 12 hours to obtain an in-situ curing composite solid electrolyte.
[0044] In this embodiment, taking the total mass of the in-situ solidified electrolyte precursor as 100%, the mass percentage of the polymerized monomer is 20%; the mass percentage of the lithium salt is 30%; the mass percentage of the functional additive is 10%; and the mass percentage of the organic solvent is 40%.
[0045] Embodiment three:
[0046] The composite solid electrolyte components include 12 parts of polymer monomers, 3 parts of lithium salts, 2 parts of nano-functional additives and 6 parts of organic solvents in parts by weight.
[0047] In this embodiment, the polymerizable monomer is a cycloalkane ether monomer or an olefin ether monomer, and the cycloalkane ether monomer includes tetrahydrofuran, 1,3-dioxolane, polyethylene glycol methyl ether methacrylate, and a mixture of polyethylene glycol methyl ether acrylate.
[0048] In this embodiment, the lithium salt includes a mixture of lithium hexafluorophosphate, lithium bis(difluorosulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide.
[0049] In this embodiment, the nano functional additive is a Lewis acid fluorine supplying additive, including nano aluminum trifluoride.
[0050] In this embodiment, the organic solvent includes a mixture of ethyl methyl carbonate, methyl formate, tetrahydrofuran and acetone.
[0051] In this embodiment, a method for preparing a composite solid electrolyte using a Lewis fluorine-donating nano-additive comprises the following steps:
[0052] A. Mixing a polymerization monomer, a lithium salt, a nano-functional additive and an organic solvent to obtain an in-situ solidified electrolyte precursor;
[0053] B. Inject the in-situ curing electrolyte precursor into the battery cell, let it stand for 1 minute under a vacuum of -80 kPa, evacuate and package it, and let it stand for 16 hours in an environment of 22°C. The pressure during curing is 1 MPa, and cure it at 50°C for 6 hours to obtain an in-situ curing composite solid electrolyte.
[0054] In this embodiment, taking the total mass of the in-situ solidified electrolyte precursor as 100%, the mass percentage of the polymerized monomer is 12%; the mass percentage of the lithium salt is 18%; the mass percentage of the functional additive is 4%; and the mass percentage of the organic solvent is 66%.
[0055] Embodiment 4:
[0056] The composite solid electrolyte components include 13 parts of polymer monomers, 3 parts of lithium salts, 2 parts of nano-functional additives and 7 parts of organic solvents in parts by weight.
[0057] In this embodiment, the polymerization monomer is a cycloalkane ether monomer or an olefin ether monomer, and the cycloalkane ether monomer includes a mixture of tetrahydrofuran, 1,3-dioxolane, and 1,4-dioxane.
[0058] In this embodiment, the lithium salt includes a mixture of lithium hexafluorophosphate, lithium bis(difluorosulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide.
[0059] In this embodiment, the nano functional additive is a Lewis acid fluorine supplying additive, including nano boron trifluoride.
[0060] In this embodiment, the organic solvent includes a mixture of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and tetrahydrofuran.
[0061] In this embodiment, a method for preparing a composite solid electrolyte using a Lewis fluorine-donating nano-additive comprises the following steps:
[0062] A. Mixing a polymerization monomer, a lithium salt, a nano-functional additive and an organic solvent to obtain an in-situ solidified electrolyte precursor;
[0063] B. Inject the in-situ solidified electrolyte precursor into the battery cell, let it stand for 1 minute under a vacuum of -80 kPa, evacuate and package it, let it stand for 40 hours in a 34°C environment, the pressure during curing is 2 MPa, and cure it at 76°C for 10 hours to obtain an in-situ solidified composite solid electrolyte.
[0064] In this embodiment, taking the total mass of the in-situ solidified electrolyte precursor as 100%, the mass percentage of the polymerized monomer is 14%; the mass percentage of the lithium salt is 16%; the mass percentage of the functional additive is 8%; and the mass percentage of the organic solvent is 62%.
[0065] Embodiment five:
[0066] The composite solid electrolyte components include 10 parts of polymer monomers, 6 parts of lithium salts, 1 part of nano functional additives and 12 parts of organic solvents in parts by weight.
[0067] In this embodiment, the polymerization monomer is a cycloalkane ether monomer or an olefin ether monomer, and the cycloalkane ether monomer includes a mixture of ethylene oxide, 1,2-propylene oxide, and 1,4-dioxane.
[0068] In this embodiment, the lithium salt includes a mixture of lithium hexafluorophosphate and lithium bis(trifluoromethylsulfonyl)imide.
[0069] In this embodiment, the nano functional additive is a Lewis acid fluorine supplying additive, including nano boron trifluoride.
[0070] In this embodiment, the organic solvent includes a mixture of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and methyl formate.
[0071] In this embodiment, a method for preparing a composite solid electrolyte using a Lewis fluorine-donating nano-additive comprises the following steps:
[0072] A. Mixing a polymerization monomer, a lithium salt, a nano-functional additive and an organic solvent to obtain an in-situ solidified electrolyte precursor;
[0073] B. Inject the in-situ solidified electrolyte precursor into the battery cell, let it stand for 1 minute under a vacuum of -80 kPa, evacuate and package it, and let it stand for 20 hours in a 24°C environment. The pressure during curing is 2 MPa, and it is cured at 60°C for 7 hours to obtain an in-situ solidified composite solid electrolyte.
[0074] In this embodiment, taking the total mass of the in-situ solidified electrolyte precursor as 100%, the mass percentage of the polymerized monomer is 16%; the mass percentage of the lithium salt is 20%; the mass percentage of the functional additive is 4%; and the mass percentage of the organic solvent is 60%.
[0075] Embodiment six:
[0076] The composite solid electrolyte components include 15 parts of polymer monomers, 4 parts of lithium salts, 3 parts of nano-functional additives and 8 parts of organic solvents in parts by weight.
[0077] In this embodiment, the polymerization monomer is a cycloalkane ether monomer or an olefin ether monomer, and the cycloalkane ether monomer includes a mixture of ethylene oxide, 1,2-propylene oxide, and tetrahydrofuran.
[0078] In this embodiment, the lithium salt includes a mixture of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(difluorosulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide.
[0079] In this embodiment, the nano functional additive is a Lewis acid fluorine supplying additive, including a mixture of nano aluminum trifluoride and nano boron trifluoride.
[0080] In this embodiment, the organic solvent includes ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and a mixture of methyl and ethyl carbonate.
[0081] In this embodiment, a method for preparing a composite solid electrolyte using a Lewis fluorine-donating nano-additive comprises the following steps:
[0082] A. Mixing a polymerization monomer, a lithium salt, a nano-functional additive and an organic solvent to obtain an in-situ solidified electrolyte precursor;
[0083] B. Inject the in-situ solidified electrolyte precursor into the battery cell, let it stand for 1 minute under a vacuum of -80 kPa, evacuate and package it, let it stand for 30 hours in a 30°C environment, the pressure during curing is 2 MPa, and cure it at 65°C for 8 hours to obtain an in-situ solidified composite solid electrolyte.
[0084] In this embodiment, taking the total mass of the in-situ solidified electrolyte precursor as 100%, the mass percentage of the polymerized monomer is 15%; the mass percentage of the lithium salt is 25%; the mass percentage of the functional additive is 5%; and the mass percentage of the organic solvent is 55%.
[0085] Comparative Example:
[0086] Compared with Example 1, no nano-functional additive is included, and the rest is the same as Example 1.
[0087] Under the same conditions, the batteries prepared in the above Examples 1-6 and the comparative example were subjected to impedance tests and cycle performance tests. The specific test methods are as follows:
[0088] Under the same conditions, the batteries prepared in the above Examples 1-6 and the comparative example were subjected to impedance tests and cycle performance tests. The specific test methods are as follows:
[0089] Battery AC impedance: The battery of each embodiment and comparative example was tested on an electrochemical workstation with an AC impedance voltage signal of 10 mV and a frequency range of 10 6 -10 -2 Hz, ionic conductivity is calculated from EIS results combined with the ionic conductivity formula;
[0090] 25℃ cycle performance test: At 25℃, the lithium-ion battery is charged to 4.2V at a current density of 1C and a constant current and voltage, with a cut-off rate of 0.05C, and left for 10 minutes. Then, it is discharged to 2.75V at a current density of 1C and left for 10 minutes. The capacity retention rate of 500 cycles is tested (the capacity retention rate is terminated when it decays to 80%).
[0091] The test results are shown in the following table
[0092] project Ionic conductivity (mS / cm) 500-week capacity retention rate Example 1 6.17 84.1 Example 2 6.78 86.2 Example 3 5.33 83.0 Example 4 5.68 84.2 Example 5 5.89 85.1 Example 6 6.59 84.9 Comparative Example 4.31 79.3
[0093] Combined with Table 1, it can be seen that compared with the battery of Comparative Example 1, the batteries of Examples 1-6 have smaller impedance and better cycle performance. This is because the batteries of Examples 1-6 all adopt a method for preparing a solid electrolyte that uses Lewis acid fluorine-donating nano-additives to achieve in-situ uniform curing and improve solid / solid interface wettability. The Lewis acid fluorine-donating additive can effectively improve lithium ion conductivity).
[0094] Comparing Examples 1 and 2, adding Lewis fluorine supply additives within a certain range can more effectively catalyze the polymerization reaction, while promoting the dissociation of lithium salts and increasing the number of lithium ion migration to improve conductivity; participating in the film-forming reaction at the negative electrode interface to form a more stable and mechanically strong LiF stable interface to improve the cycle performance. At the same time, the nano-fluorine supply additive can form a more wettable solid / solid interface with the positive and negative electrode materials and the polymer, which can enhance the mechanical strength of the solid electrolyte and stabilize the cycle performance of the battery.
[0095] Comparing Examples 1 and 3-6, increasing the concentration of lithium salt is beneficial to improving lithium ion conductivity and has a certain positive effect on long cycle performance.
[0096] In the present invention, no additional initiator is added to the raw materials for preparing the in-situ solidified solid electrolyte. The lithium salt is unstable and decomposed into Lewis acid under heating. The Lewis acid is used to efficiently initiate the ring-opening of the cyclic ether for polymerization reaction. No initiator residue is left, and no additional side reactions will occur to cause the battery performance to deteriorate. Specifically, in the absence of external heating conditions, the heat of dissolution of lithium salts such as lithium hexafluorophosphate is sufficient to promote its partial decomposition and release a small amount of phosphorus pentafluoride. In the precursor solution, phosphorus pentafluoride combines with trace water to form H + (PF5OH) - , H + (PF5OH) - The DOL monomer is induced to transform into a reactive second oxonium ion through rapid protonation, and the DOL monomer is repeatedly inserted into the oxonium ion to grow the polymer chain.
[0097] The nano-functional additive in the present invention is a Lewis fluorine-supplying additive, which has three main functions: on the one hand, nano-AlF3 has a Lewis acid center, which can be hydrolyzed to form a Lewis acid under heating and other conditions, and can effectively catalyze the ring-opening polymerization reaction to improve the polymerization efficiency; the Lewis fluorine-supplying additive has a strong adsorption effect on lithium salt anions, can promote the dissociation of lithium salts, inhibit the formation and migration of anion clusters [Li(TFSI)2]-, and then provide more free Li+, improve the ion conductivity of the electrolyte and the number of lithium ion migration, and can reduce the electrode pole to achieve high rate performance of the battery; the nano-material can be well dispersed on the surface of the positive and negative electrode materials to form a good solid / solid interface with the polymer electrolyte. At the same time, the nano-material has a large specific surface area and a high catalytic activity. The nano-additive can effectively adsorb the polymerization monomer of the polymerization reaction, and as a polymerization reaction catalytic center, it makes the in-situ polymerization reaction more uniform and forms a solid electrolyte with uniform polymerization reaction and high ion conductivity.
[0098] In summary, the preparation method of the present invention is simple, and the prepared composite solid electrolyte, when used in lithium-ion batteries, has the characteristics of no need for additional initiators, uniform polymerization reaction, high ion conductivity, etc., and can improve the stability, rate and cycle performance of semi-solid lithium-ion batteries.
[0099] As described above, the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application.
Claims
1. A composite solid electrolyte prepared by using Lewis fluorine-donating nano additives, characterized in that: The composite solid electrolyte components include 10-20 parts of polymer monomers, 2-6 parts of lithium salts, 1-4 parts of nano functional additives and 5-12 parts of organic solvents in parts by weight.
2. The method of preparing a composite solid electrolyte by using a Lewis fluorine-donating nano-additive according to claim 1, characterized in that: The polymerizable monomer is a cycloalkane ether monomer or an olefin ether monomer, and the cycloalkane ether monomer includes at least one of ethylene oxide, 1,2-propylene oxide, tetrahydrofuran, 1,3-dioxolane, 1,4-dioxane, polyethylene glycol methyl ether methacrylate, and polyethylene glycol methyl ether acrylate.
3. The method of preparing a composite solid electrolyte by using Lewis fluorine-donating nano-additives according to claim 1, characterized in that: The lithium salt includes any one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(difluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, and lithium difluorooxalatoborate, or a combination of at least two thereof.
4. The method of preparing a composite solid electrolyte by using Lewis fluorine-donating nano-additives according to claim 1, characterized in that: The nano functional additive is a Lewis acid fluorine supply additive, including any one of nano aluminum trifluoride and nano boron trifluoride or a combination of the two.
5. The method of preparing a composite solid electrolyte by using Lewis fluorine-donating nano-additives according to claim 1, characterized in that: The organic solvent includes any one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl formate, tetrahydrofuran, acetone, methyl pyrrolidone, and acetonitrile, or a combination of at least two thereof.
6. A method for preparing a composite solid electrolyte by using Lewis fluorine-donating nano additives, characterized in that: The following steps are involved: A. Mixing a polymerization monomer, a lithium salt, a nano-functional additive and an organic solvent to obtain an in-situ solidified electrolyte precursor; B. Inject the in-situ curing electrolyte precursor into the battery cell, let it stand for 1 minute under a vacuum of -80 kPa, and let it stand for 12-48 hours in an environment of 20-35°C after vacuum packaging. The pressure during curing is 0.6-3 MPa, and it is cured at 45-80°C for 4-12 hours to obtain an in-situ curing composite solid electrolyte.
7. The method for preparing a composite solid electrolyte by using Lewis fluorine-donating nano-additives according to claim 6, characterized in that: Taking the total mass of the in-situ solidified electrolyte precursor as 100%, the mass percentage of the polymerized monomer is 10%-20%; the mass percentage of the lithium salt is 15-30%; the mass percentage of the functional additive is 0%-10%; and the mass percentage of the organic solvent is 40%-75%.
Citation Information
Cited By
Composite electrolyte and preparation method and application thereof
CN120834288A